Study guide for the new trading for a living : Psychology, Discipline trading tools and systems, risk control, Trade management - Elder, Alexander ([Place of publication not identified] : Wiley & Sons, Limited, John, 2013)
Test your trading knowledge and skills-without risking any money You may read the best trading book, but how much of that knowledge will you retain a week later? This is why you need this Study Guide for The New Trading for a Living. It''ll give you a firmer grasp of the essential trading rules and skills. This Study Guide, based on the bestselling trading book of all time, was created by its author to help you master the key points of his classic book. The Study Guide''s 170 multiple-choice questions are divided into 11 chapters, each with its own rating scale. They cover the entire range of.
Recommended ReadingTHREE Classical Chart Analysis; Rating Yourself; Recommended Reading; FOUR Computerized Technical Analysis; Rating Yourself; Recommended Reading; FIVE Volume and Time; Rating Yourself; Recommended Reading; SIX General Market Indicators; Rating Yourself; Recommended Reading; SEVEN Trading Systems; Rating Yourself; Recommended Reading; EIGHT Trading Vehicles; Rating Yourself; NINE Risk Management; Rating Yourself; Recommended Reading; TEN Practical Details; Rating Yourself; ELEVEN Good Record-Keeping; Rating Yourself; Afterword; Sources; About the Author; EULA.
Includes bibliographical references at the end of each chapters.
Print version record.
Keywords: Stock exchanges; Stocks -- Risk assessment; Trading rooms (Finance); Consumers; Consumption (Economics); Finance, Personal; BUSINESS & ECONOMICS -- Finance; Electronic books; Electronic books